The Contribution of Cyberloafing and Perceived Peer Support to Academic Procrastination Behavior of Final Year Students - Wilda Oktaviana; Mardianto; oktaviana, wilda (In Trend : International Journal of Trends in Global Psychological Science and Education, 2024)
Students often do other activities that are not related to college assignments, so students often delay working on their thesis which is called procrastination. Procrastination behavior is influenced by several factors such as internet abuse that is not related to college assignments called cyberloafing, and low support from peers. This study aims to determine the contribution of cyberloafing and perceptions of peer support to the academic procrastination behavior of final year students. This study uses a quantitative approach. The sample in this study was selected using a purposive sampling technique of 200 respondents. Procrastination was measured using the Academic Procrastination Scale (APS). Cyberloafing was measured using the cyberloafing scale. Peer support was measured using the Social Previsions Scale (SPS). The results of the study identified that there was a contribution of cyberloafing to academic procrastination of 28% to academic procrastination. Peer support did not contribute significantly to academic procrastination, this could happen because social support is not one of the factors that can influence academic procrastination behavior in students who are working on their thesis. Low cyberloafing can reduce procrastination behavior in students in Padang city.